Avian communities of betel nut agroforestry and secondary forest in Taiwan - Jo-Szu Tsai; Chia-Hao Chang; Ping Huang; Jerome Chie-Jen Ko; Fu-Hsiung Hsu (Biodiversity Data Journal)
Betel nut agroforestry had quickly grown to occupy more than 1% of the land in Taiwan, often taking the place of secondary forests. While agroforestry systems can help mitigate biodiversity loss by preserving habitat structure and providing essential ecological services, the ecological role of betel nut plantations — particularly their impact on avian communities — remains largely understudied. Birds, as sensitive indicators of environmental change, offer valuable insights into habitat quality and biodiversity health. To address this knowledge gap, we conducted standardised point count surveys to collect data on bird species composition and abundance.This was the first avian dataset focused on betel nut agroforestry, providing detailed bird occurrence data for betel nut plantations and secondary forests. The dataset is particularly useful for understanding how agriculture alters ecological services in human-modified landscapes. Data were collected during the breeding seasons (March to May) of 2015 and 2016 across 80 sites in four counties of central Taiwan. Each site included five sampling points, with avian community data recorded twice per season at each point. This publicly available dataset on GBIF offers valuable insights into avian biodiversity and habitat use in agricultural ecosystems.